Imminent risk of fracture after fracture. Issue 3 (March 2017) - Johansson, H.; Siggeirsdóttir, K.; Harvey, N.; Odén, A.; Gudnason, V.; McCloskey, E.; Sigurdsson, G; Kanis, J.
Abstract Summary The risk of major osteoporotic fracture (MOF) after a first MOF is increased over the whole duration of follow-up, but the imminent risk is even higher. If the acute increment in risk in the few years following MOF is amenable to therapeutic intervention, then immediate short-term treatments may provide worthwhile clinical dividends in a very cost-effective manner. Introduction A history of fracture is a strong risk factor for future fractures. The aim of the present study was to determine whether the predictive value of a past MOF for future MOF changed with time. Methods The study was based on a population-based cohort of 18, 872 men and women born between 1907 and 1935. Fractures were documented over 510, 265 person-years. An extension of Poisson regression was used to investigate the relationship between the first MOF and the second. All associations were adjusted for age and time since baseline. Results Five thousand thirty-nine individuals sustained one or more MOFs, of whom 1919 experienced a second MOF. The risk of a second MOF after a first increased by 4% for each year of age (95% CI 1.02–1.06) and was 41% higher for women than men (95% CI 1.25–1.59). The risk of a second MOF was highest immediately after the first fracture and thereafter decreased with time though remained higher than the population risk throughout follow-up. For example, 1 year after the first MOF, the risk of a second fracture was 2.7 (2.4–3.0) fold higher than the population risk. After 10 years, this risk ratio was 1.4 (1.2–1.6). The effect was more marked with increasing age. Conclusions The risk of MOF after a first MOF is increased over the whole follow-up, but the imminent risk is even higher. If the acute increment in risk in the few years following MOF is amenable to therapeutic intervention, then immediate short-term treatments may provide worthwhile clinical dividends in a very cost-effective manner, particularly in the elderly.